Rate-dependent low cycle fatigue and ratcheting of 25Cr2MoVA steel under cyclic pulsating tension. (3rd September 2018) - Zheng, Xiaotao; Wang, Jiqiang; Gao, Jiuyang; Ma, Linwei; Yu, Jiuyang; Xu, Jianmin
ABSTRACT: Low cycle fatigue and ratcheting deformation of 25Cr2MoVA steel under cyclic tension were tested at 550°C. The effects of stress rates for 0·1, 0·5, 2·5, 5, 10, and 40 MPa s −1 on ratcheting effect and fracture appearance were discussed systematically. Results indicate that the steady static creep rate very approaches to the ratcheting strain rates for 0·1 MPa s −1, but it is obviously greater than those of greater stress rates tested. Moreover, the steady ratcheting strain rate reduces rapidly with increasing the frequency when the frequency is less than 36·8 h −1, and then changes slightly for the greater frequency. This implies the steady ratcheting rate of 25Cr2MoVA is approximately rate-independent when the stress rate is greater than 10 MPa s −1 . Additionally, there are some microvoids in the central fibrous regions of specimens under static creep and cyclic tension with 0·1, 0·5, and 5 MPa s −1, but very few microvoids for the specimen under cyclic tension with 10 MPa s −1 can be observed. Furthermore, the low cycle fatigue life is relatively short when the stress rate is less than 10 MPa s −1, but it enhances exponentially subsequently.